Corporate Social Responsibility Disclosure : Profitabilitas dan Karakteristik Perusahaan - Teguh Erawati; Ila Faizun Nisa' (Jurnal Literasi Akuntansi, 2024)
Purpose: This research aims to prove the influence of profitability and company characteristics on Corporate Social Responsibility (CSR) Disclosure. Profitability is proxied through ROA, ROE, NPM and characteristics are proxied through company size, board of commissioners size and company age. Method: The data used is secondary data obtained through the official website of the Indonesian Stock Exchange (BEI), with a research sample of plastic and packaging sub-sector companies in the 2018-2022 period. The sampling method is purposive sampling. The total population is 14 plastic and packaging sub-sector companies listed on the IDX, 8 companies are the sample. Data were analyzed using SPSS 25.00. Finding: The results of research on the T-test state that profitability projected on ROA has no effect on CSR Disclosure with a sig value. ROA 0.396 ≥ 0.05, ROE has no effect on CSR Disclosure with a sig value. ROE 0.744 ≥ 0.05. NPM has no effect on CSR Disclosure with a sig value. NPM 0.064 ≥ 0.05. The projected company characteristics of company size have no effect on CSR Disclosure with a t-count value of -2.451 ≤ t-table 2.037 and a βeta value of -0.074. The size of the board of commissioners has no effect on CSR Disclosure with a sig value. Board of Commissioners 0.438 ≥ 0.05 and company age has a positive effect on CSR Disclosure with a sig value. 0.009 ≤ 0.05. Novelty: This research developes research from Putri Tri K., Reka Maiyarni, Wiwik Tiswiyanti (2019) by adding independent variables, namely Net Profit Margin (NPM), size of the board of commissioners and company age. This research was used to test the influence of the six independent variables, namely ROA, ROE, NPM, Size, size of the board of commissioners and company age on Corporate Social Responsibility Disclosure as the dependent variable.